2022
DOI: 10.1177/07482337221076248
|View full text |Cite
|
Sign up to set email alerts
|

Occupational lead exposure is an independent modulator of hypertension and poor pulmonary function: A cross-sectional comparative study in lead-acid battery recycling workers

Abstract: Blood lead level (BLL) is the primary biomarker for lead-exposure monitoring in occupationally exposed workers. We evaluated occupational lead-exposure (OE) impact on cardiopulmonary functions in lead-acid battery recycling unit workers. Seventy-six OE cases and 30 control subjects were enrolled for questionnaire-based socio-demographic, dietary, tobacco usage, and medical history data. Anthropometric measurements, systolic and diastolic blood pressure (SBP and DBP), and pulmonary function tests were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…At the same time, we found that born in other countries, citizen in other ways, longer stays in the United States, under high school graduate, living with a companion, and total number of people in the family ≤3 might be risk factors associated with blood lead level. Although there have been few studies to explain why people with these characteristics had higher blood lead levels, we know that lead exposure is occupational and is associated with poor living conditions ( 28 , 29 ), so we speculate that the participants in this study with higher blood lead levels might have been at a higher risk of lead exposure due to their work and living conditions. For example, people with lower levels of education might be less aware of protection at work ( 30 ).…”
Section: Discussionmentioning
confidence: 85%
“…At the same time, we found that born in other countries, citizen in other ways, longer stays in the United States, under high school graduate, living with a companion, and total number of people in the family ≤3 might be risk factors associated with blood lead level. Although there have been few studies to explain why people with these characteristics had higher blood lead levels, we know that lead exposure is occupational and is associated with poor living conditions ( 28 , 29 ), so we speculate that the participants in this study with higher blood lead levels might have been at a higher risk of lead exposure due to their work and living conditions. For example, people with lower levels of education might be less aware of protection at work ( 30 ).…”
Section: Discussionmentioning
confidence: 85%
“…The use of body mass index as a measure of health status of humans is quite popular as it gives an indication of the vulnerability of humans to certain chronic diseases such as diabetes, hypertension and cardiovascular diseases (Ge et al, 2021; Yadav et al, 2022; Yoon et al, 2021). The normal range of body mass index for a healthy man was 18–24.9 kg/m 2 (Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of bilirubin in the blood have been associated with adverse medical conditions such as hepatitis, cirrhosis, haemolytic jaundice and obstruction of the biliary tract (Ding et al, 2021; Hamoud et al, 2018). The significant lower levels of platelets in the exposed subjects than the controls could be an indication that the subjects were exposed to increased risks of blood clotting since platelets play an important role in blood clotting (Chokpitakkul, 2022; Yadav et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we also found that AF/AFL mortality and DALYs attributable to lead exposure are on the rise in low-and low-middle-SDI countries for both male and female populations. Previous studies determined that lead exposure was strongly associated with hypertension [23], acute ischemic stroke [24], and heart failure [25], and that reducing lead exposure can result in substantial advantages for the adult population [26]. Lead exposure should be a prioritised topic, especially in nations and regions with a low or low-middle SDI.…”
Section: Additional Materialsmentioning
confidence: 99%